Fast and robust protocol for prenatal diagnosis of mucopolysaccharidosis type II - Leistner-Segal, Sandra; Brusius-Facchin, Ana Carolina; Gus, Rejane; Burin, Maira; Sanseverino, Maria Teresa; Magalhães, José Antônio; Giugliani, Roberto (Clinical and Biomedical Research, 2014)
Introduction: Mucopolysaccharidosis type II (MPSII) is an X-linked lysosomal disorder caused by deficiency of iduronate-2-sulfatase (IDS). In this study, we proposed a new protocol for prenatal diagnosis, using DNA obtained from amniotic fluid cells that did not attach to the bottom of the culture flask after the first medium change. Methods: Four pregnant MPS II carriers were referred to the Medical Genetics Service of Hospital de Clinicas dePorto Alegre for a prenatal diagnosis and identification of the disease, which were performed by polymerase chain reaction (PCR) amplification, restriction fragment length polymorphism, and sequencing according to the mutation previously found in the family. Results: The analysis indicated the absence of mutation in three fetal materials and the presence of mutation in one case. Concomitantly, cytogenetic and biochemical analyses were performed after 12 days of cell culture, and only one case showed absence of enzyme activity, confirming the molecular analysis. Conclusions: This diagnostic protocol designed to provide more robust results and safer genetic counseling suggests that DNA obtained from floating amniotic fluid cells can be used as a source of fetal material to allow a faster alternative for prenatal care through molecular analysis. Determination of IDS gene mutation in fetal amniotic fluid cells together with IDS enzyme activity testing is a rapid, sensitive and accurate method for prenatal diagnosis of MPS II for high-risk pregnant women.